The Russian-Turkish relations in the context of syrian crisis - Yermekbayev, A.A.; Abzhaparova, L.Z.; Iztayeva, V.A. (Opción, 2019)
In this article problems of the Russian-Turkish relations at the present stage in the context of the Syrian crisis are analyzed via comparative qualitative research methods. In result, development of the relations in the sphere of economy, power, naturally have the positive impact on the bilateral relations, however, they are not capable to pull together a different vision of the situation on many moments of international policy. In conclusion, Turkey and Russia seek to strengthen the influence in the region, and this uncompromising position of Moscow and Ankara led to an escalation of the relations between two powers.